Principals Strategies for Merdeka Curriculum Implementation in Early Childhood Education: Strategi Kepala Sekolah dalam Implementasi Kurikulum Merdeka pada PAUD - Eva Kristina; Munawar Munawar; Cut Khairani; Siraj Siraj; Najmuddin ⁠ Najmuddin (Academia Open, 2026)
General Background: The implementation of the Merdeka Curriculum in Early Childhood Education requires strategic leadership to support learning transformation. Specific Background: Variations in school readiness, human resource capacity, and local conditions present challenges in Aceh Tamiang Regency. Knowledge Gap: Previous studies have largely focused on primary and secondary education, with limited attention to principal strategies in early childhood education contexts. Aims: This study aims to analyze principals’ strategies in implementing the Merdeka Curriculum at the PAUD level based on Mintzberg’s strategic dimensions: plan, ploy, pattern, and perspective. Results: Using a qualitative multisite case study approach in three kindergartens, the findings reveal that principals align school vision with the Pancasila student profile, develop collaborative programs, empower teachers through training and mentoring, implement consistent monitoring and evaluation, and foster a child-centered learning culture. Novelty: This study extends the application of Mintzberg’s strategic framework to early childhood education leadership within the Merdeka Curriculum context. Implications: The findings provide a practical reference for principals and policymakers in designing contextual, collaborative, and sustainable leadership strategies to support curriculum implementation in early childhood education. HIGHLIGHTS • Alignment of institutional vision with national student character framework guides implementation• Teacher empowerment conducted through structured training and collaborative learning communities• Continuous evaluation and routine practices sustain child-centered learning environments KEYWORDS Principals Strategies; Merdeka Curriculum; Early Childhood Education; Educational Leadership; Curriculum Implementation